Examining The Mediating Effect Of Work Motivation In The Relationship Between Supervisory Reward Power And Employees’ Job Outcome - Wong, Lindsey; Victoria, Jonathan; Hana, Hamidi (2011)
A growing number of studies on supervisory reward power and work motivation have been carried out due to the realization of the effect of a demanding working environment in today’s competitive world. An organization that has a proper reward system in place and motivates its employees may help to increase employee performance and retention. While there have been many studies of employees’ job outcome in terms of task performance in organizations, little known studies have examined the linkage of supervisory reward power with employees’ job outcome where the effect of work motivation, as a mediator, is included (Hsi & Tso, 2008). This study was conducted to perceive the mediating effect of work motivation in the relationship between supervisory reward power and employees’ job outcome. A survey research method was used to gather 118 usable questionnaires from a private company in Sarawak, Malaysia. The outcome of Pearson Correlation analysis indicated that there is a correlation between supervisory reward power, work motivation and employees’ job outcome. Furthermore, the study results supported the mediating effect of work motivation between supervisory reward power and employees’ job outcome.